A educação financeira nas séries iniciais do ensino fundamental - MIRANDA, João Vagno da Costa Silva (2020)
The financial education of a child includes components that go beyond the economic concepts, with important special attention to thepreparation of the newest concerning the correct use of their economies to grow responsible and knowledgeable. The easiest way starts early, especially in relation to financial security through money. Thinking about this problem, this article built through a literature review, has the main objective to show the importance of financial education in childhood.